Analisis Strategi Marketing Produk Pembiayaan Murabahah dalam Meningkatkan Jumlah Nasabah : Studi Kasus: BMT Agam Madani Nagari Batu Taba Kecamatan Ampek Angkek - Chrisvi Febriani Adha; Sandra Dewi; Zulhelmi Zulhelmi; Rahmi Rahmi (Lembaga Pengembangan Kinerja Dosen, 2026)
Marketing strategies are also needed by BMT Agam Madani Nagari Batu Taba to increase the number of customers for all its products, especially in murabahah financing. Murabahah financing to customers who need funds to start or develop their businesses, especially for residents of Nagari Batu Taba who are engaged in the convection, trade, and agriculture sectors. This study aims to find marketing methods that can increase the number of customers for murabahah financing at BMT Agam Madani Nagari Batu Taba. In this study, the method applied is field research with a qualitative approach. The data collected comes from primary and secondary sources through observation, interviews, and documentation. Data processing and analysis are carried out through three steps, namely data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the number of customers for murabahah financing products has decreased. This decline is due to the lack of socialization and promotion activities and the presence of other more well-known financial institutions that are a threat to BMT in competing. Word of mouth marketing methods or direct invitations from mosques are considered less effective. Therefore, BMT Agam Madani Nagari Batu Taba needs to strengthen its marketing strategy known as 4P: product, price, place, and promotion. Especially in terms of promotion, it needs to be integrated with digital methods to reach more customers and increase sales.